2017
DOI: 10.3126/jcmsn.v13i1.16668
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implants and General Dental Practitioners of Nepal: A study of existing knowledge and need for further education

Abstract: Background & Objectives: The use of dental implants in partially or completely edentulous patients has proved effective and an accepted treatment modality with predictable long-term success. Dental implants are becoming a popular choice for replacing the missing teeth because of increased awareness about implants both in dentists and patients. The objective of the study was to assess the basic knowledge and education about dental implants among general dental practitioners (GDPs) of Nepal.Materials & M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…About 69% of our study participants preferred dental implant as a treatment to replace missing tooth. Similar findings was seen in a study by Rathod V et al 12 and Shah RJ et al 18 Preference for dental implants as tooth replacement option could be due to increasing acceptance of this treatment among the dentists. Though about one fourth of the dentists had undergone extra implant training, 68.1% of them could only be seen practicing dental implants.…”
Section: Discussionsupporting
confidence: 85%
“…About 69% of our study participants preferred dental implant as a treatment to replace missing tooth. Similar findings was seen in a study by Rathod V et al 12 and Shah RJ et al 18 Preference for dental implants as tooth replacement option could be due to increasing acceptance of this treatment among the dentists. Though about one fourth of the dentists had undergone extra implant training, 68.1% of them could only be seen practicing dental implants.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it has become compulsory for the GDPs to be well-knowledge with dental implants. 8 Definition of successful implants is constantly changing. Currently, successful implant therapy is defined in terms of both functional and psychosocial acceptance by patients.…”
Section: Discussionmentioning
confidence: 99%
“…zirconium dioxide or aluminium oxide). [3][4][5][6][7][8] Surfaces are normally roughened (Microporous) through use of surface preparation (e.g. sand blasting and acid etching) rather than being coated to increase the surface area available for osseointegration (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Other study showed an average, 80 out of 110 General dental practitioners had basic knowledge about implant dentistry and 65.5% were not aware about advance surgical procedures like sinus lift, guided bone regeneration etc., for dental implant surgery. 22 Only 9 (6.3%) interns perceived that they were well prepared in replacing the teeth with implants. 23 In an other study, 39.11% of the dental interns were very confident regarding the knowledge of implant procedures.…”
Section: Discussionmentioning
confidence: 99%